2019
DOI: 10.1002/cncr.32368
|View full text |Cite
|
Sign up to set email alerts
|

First‐line atezolizumab in addition to bevacizumab plus chemotherapy for metastatic, nonsquamous non–small cell lung cancer: A United States–based cost‐effectiveness analysis

Abstract: BACKGROUND:The IMpower150 trial found that adding atezolizumab to the combination of bevacizumab and chemotherapy improved survival for patients with metastatic, nonsquamous non-small cell lung cancer (NSCLC). However, considering the high cost of immunotherapy, there is a need to assess its value by considering both efficacy and cost. The current study evaluated the cost-effectiveness of atezolizumab in the first-line setting for the treatment of patients with metastatic NSCLC from the US payer perspective. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 34 publications
2
72
0
3
Order By: Relevance
“…Previous studies on antiangiogenesis therapeutic drugs mostly excluded patients with squamous cell carcinoma because of the potential risk of life‐threatening pulmonary hemorrhage [17–20]. However, the present study included patients with lung squamous cell carcinoma, but no fatal bleeding events were observed.…”
mentioning
confidence: 88%
“…Previous studies on antiangiogenesis therapeutic drugs mostly excluded patients with squamous cell carcinoma because of the potential risk of life‐threatening pulmonary hemorrhage [17–20]. However, the present study included patients with lung squamous cell carcinoma, but no fatal bleeding events were observed.…”
mentioning
confidence: 88%
“…Chinese and US studies were inconclusive, each with both positive and negative studies (87)(88)(89)(90)(91)(92)(93). However, a recent cost-effectiveness study from the IMpower 150 trial, using a Markov model, showed improved cost-effectiveness of an atezolizumab, bevacizumab, carboplatin, and paclitaxel (ABCP) combination over bevacizumab, carboplatin, and paclitaxel (BCP) and carboplatin and paclitaxel (CP) in the first-line treatment of patients with metastatic NSCLC (94). It is difficult to directly extrapolate to mesothelioma patients from NSCLC data, since people with mesothelioma are generally older, but conversely have fewer smoking induced comorbidities.…”
Section: Current Recommendations For Use Of Anti-angiogenic Strategiementioning
confidence: 99%
“…The characteristics of all included studies are presented in S1 Table. Most of the studies were conducted in 2019 [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Studies were conducted from countries all over the world, with ten from the USA [22-27, 29, 30, 32, 33], seven from China (one from HongKong) [34][35][36][38][39][40][41], two from Canada [20,37], and one each from Australia [31], France [28] and Switzerland [21]. Most studies were assessed from the perspective of health care system (N = 12) [20-22, 25, 26, 28-31, 35, 37, 40], some used a payer perspective (N = 8) [23,24,27,32,33,38,39,41], and the remainder used a perspective of society (N = 1) [34] and hospital authority (N = 1) [36].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%